Diagnostic value of FNAC combined with BRAFV600E mutation detection in Hashimoto’s thyroiditis complicated with papillary thyroid carcinoma - Fu, Jingyao; Yin, Xiangdang; Wang, Xiaochun; Xiao, Siqi; Wu, Xianji; Duan, Chengcheng; Yu, Wenxi; Zhang, Guang (Frontiers in Endocrinology, 2024)
Background: This study aimed to analyze the effect of preoperative fine needle aspiration cytology (FNAC) combined with BRAF V600E mutation detection as compared to that of fine needle aspiration cytology alone on the diagnostic performance of papillary thyroid carcinoma (PTC) combined with Hashimoto's thyroiditis (HT). Method: Patients with thyroid nodules in Hashimoto's thyroiditis, who underwent fine-needle aspiration cytology examination and BRAF V600E mutation detection in the puncture eluate at the outpatient clinic, were selected. Finally, 122 patients received surgical treatment and were included in the study. We used postoperative pathological results as the gold standard. Accordingly, we compared the sensitivity, specificity and accuracy of preoperative FNAC alone and FNAC combined with BRAF V600E mutation detection in for the diagnosis of PTC combined with HT. Results: For PTC patients with HT, the sensitivity of FNAC diagnosis was 93.69%, the specificity was 90.90% and the accuracy was 93.44%. However, the sensitivity, specificity and accuracy of FNAC combined with BRAF V600E mutation detection were 97.30%, 90.90% and 96.72%, respectively. Therefore, combined detection can improve the sensitivity and accuracy of diagnosis (p<0.05). Conclusion: FNAC combined with eluent BRAF V600E mutation detection can improve the sensitivity and accuracy of diagnosis of PTC in the background of HT.